Data are data: Do we need a randomized trial of transcatheter aortic valve replacement for bicuspid valves?. Issue 6 (29th November 2022) - Ueyama, Hiroki; Block, Peter C.
Key Points: No randomized trials have been done for TAVR in bicuspid aortic valve (BAV) and probably will never be done. TAVR for BAV has a similar risk profile to tricuspid aortic valve patients except for a higher risk of permanent pacemaker implantation at 30 and 180 days after the index procedure. Further real‐world data are needed to refine patient selection, procedural technique, and lifetime planning of intervention.